Visual-spatial dimensions of modern residential buildings, experience of the Nordic region - Ile, Una (Landscape Architecture and Art, 2021)
The visual-spatial dimensions of architecture are constantly changing, architects and urban planners are aware and understand the need for a healthy, active, vibrant public outdoor space, creating viable, economically and rationally suitable living spaces in the urban environment [12]. A comprehensive approach to sustainable architecture and design with a green structure combines a high-quality urban environment. In modern architecture, one of the perspective directions in the development of visual-spatial environment and structural forms is related to the active and continuous synthesis of the design and construction process in the urban environment [13; 4]. In recent years, the tendencies of rationalism and commercial nature based on technological progress have entered architecture and create a need for the architects to purposefully cooperate with the urban planners in the elaboration of development plans. The format of mutual cooperation brings together and rationally balances various dimensions of the urban environment in a compact visual-spatial structure. Thus, the aim of the research is to determine the visual-spatial dimensions of modern residential buildings in the context of sustainable urban development.